A coupled stress analysis of the steam generator tube considering the influence of the fluid flow and heat transfer in the primary and secondary sides. (5th August 2015) - Sun, Baozhi; Zheng, Lusong; Yang, Longbin; Li, Yanjun; Shi, Jianxin; Liu, Shanghua; Qi, Hongliang
Abstract: This work established a simplified physical model of an actual steam generator, including the primary and secondary fluid domains, the tubes and the tube support plates (TSPs). The coupled system of fluid flow and heat transfer in the steam generator was simulated under rated operating condition using computational fluid dynamics (CFD). A thermal analysis and a static structural analysis of the tube and TSPs were conducted through flow-solid interaction (FSI) considering the influence of fluid flow and heat transfer. The thermal stress under temperature load, the mechanical stress under pressure load and the coupled stress under both the loads were calculated. The results show that the coupled stress is the combined effect of the thermal and mechanical stresses. The thermal stress depends on both the temperature change and the effects of the TSPs, while the mechanical stress is associated with the hydrostatic pressure. At the TSPs, the circumferential and radial stresses of the tube are uneven, with stress corrosion and high cycle fatigue occurring at these sites. The calculated results are consistent with actual measured values and existing literature results, and the conclusions of this paper can provide a reference for optimizing steam generator structures. Graphical abstract: Highlights: A simplified physical model of an actual steam generator is established. The thermal-hydraulic characteristics of steam generator are simulated using CFD. A steady-state thermal analysis and a structural static analysis are conducted. The thermal stress, mechanical stress and coupled stress distributions are examined. The degradation and stress corrosion failure positions of the tube are predicted.